(untitled) (Swiss Medical Weekly, 2017)
Exertional dyspnoea is a leading symptom in patients with pulmonary arterial hypertension (PAH). Patients suffering from PAH report poor quality of life, have skeletal muscle dysfunction and in the absence of advanced medical therapy deteriorate progressively due to right heart failure which can lead to death. For decades, patients with PAH were advised to avoid exercise in fear of exacerbated right heart failure. Recently, it has been shown that a highly supervised rehabilitation programme in expert centres leads to significant improvements in symptoms, quality of life, exercise capacity and may even enhance haemodynamics in selected stable patients treated with advanced regimens of PAH-targeted drugs. As a consequence of these promising results, pulmonary rehabilitation performed in an expert centre has been included in recent guidelines. The underlying mechanisms are not completely understood, but positive effects can be measured in different organ systems such as skeletal muscles, the cardiopulmonary system and immune system (inflammation), and also on the psychological level. Thus, improvements in 6-minute walking distance (6MWD), peak oxygen uptake (VO2 peak), muscle strength and muscle endurance, as well as physical and mental quality of life scores (SF-36 questionnaire) have been shown. Different training protocols have been used. Essential are qualified patient selection in expert centres, a low workload endurance and dumbbell (weight lifting) training avoiding strenuous exercise and exhaustion, thorough patient education and close supervision by experts especially during the first weeks. Adverse events may occur (e.g., pre-/syncope, arrhythmia, respiratory infections). PAH patients tend to overestimate their physical capacity, not perceiving their own limits properly, which makes education and expert advice even more important as exercise training can also worsen the right heart failure. Therefore, a core issue of the multidisciplinary rehabilitation is the close cooperation between the experienced rehabilitation clinic offering a specialised programme for PAH patients and the PAH expert centre, which takes care of the patient and is thoroughly involved in the training programme. Further multicentre international randomised trials are needed to evaluate whether this specialised programme is feasible within different healthcare systems and to assess long term effects and survival.